Dinner at Dan : biblical and archaeological evidence for sacred feasts at Iron Age II Tel Dan and their significance - Greer, Jonathan S. (Culture and History of the Ancient Near East, 2013)
In Dinner at Dan , Jonathan S. Greer provides biblical and archaeological evidence for sacred feasting at the Levantine site of Tel Dan from the late 10th century - mid-8th century BCE. Biblical texts are argued to reflect a Yahwistic and traditional religious context for these feasts and a fresh analysis of previously unpublished animal bone, ceramic, and material remains from the temple complex at Tel Dan sheds light on sacrificial prescriptions, cultic realia, and movements within this sacred space. Greer concludes that feasts at Dan were utilized by the kings of Northern Israel initially to unify tribal factions and later to reinforce distinct social structures as a society strove to incorporate its tribal past within a monarchic framework.